O cultivo intensivo do milho : consequências nos aspectos ambientais e técnicos na região centro-oeste de Sergipe - Silva, Grazielle Nascimento (2014)
The present study aims to analyze how different technological levels interfere in agriculture land use relations in Assentamento Oito de Outubro and Riachão Farm in the municipality of Simão Dias/SE, due to the economic evolution of maize. These areas were chosen because of the following criteria: class of similar soils in the region, areas with a high use of technology and properties that exploit the corn crop. For this research be made were conducted: data collection agencies in the agricultural context for the information regarding the evolution of productivity and corn grown in Sergipe; analysis of mechanical resistance to penetration (RMP) employed to assess compaction, density and fertility parameters; Soil and analysis of the average month temperature and rainfall for the period 2010 to 2013 levels of corn yield to relate the environmental factor with corn production. Thus, this study presents results based on field sampling and literature which describe the panorama for agricultural development in the municipality of Simão Dias / SE aiming at the production of corn that has significant technological growth in the State. It was observed that Fazenda Riachão promoted lower values of resistance penetration and bulk density because of the soil use in relation to Assentamento Oito de Outubro. Assentamento Oito de Outubro obtained values above 3.0 MPa at a depth interval of 10-15 cm deep, which can infer that this resistance is a indicative of possible compression and this situation may present some limitations to the development of corn. In relation to the interviews, it was noted that the farmer knowledge affects practices in agriculture that are essential for economic gains, another limiting factor is the storage of grain to market, affecting the values and sales in postharvest. In the analysis of pluviometry it was verified that it is an important tool to analyze how to perform planting in drought times. It is concluded that the modern agriculture process from Simão Dias obeys the technological changes of agribusiness and is based on an intensive use of mechanization in corn farming, using agrochemical inputs with investments in financial capital and, consequently, the process is modified to adapt planting up to modern highly productive plantations.